1989
DOI: 10.1016/0735-1097(89)90092-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease morbidity and mortality in hypercholesterolemic men predicted from an exercise test: The lipid research clinics coronary primary prevention trial

Abstract: A positive exercise electrocardiogram (ECG) has been proved to predict cardiovascular events in asymptomatic normolipidemic men. To study whether it is also predictive for hypercholesterolemic men, data from 3,806 asymptomatic hypercholesterolemic men in the Lipid Research Clinics Coronary Primary Prevention Trial were analyzed. All the men had performed a submaximal treadmill exercise test at baseline, before they were assigned to the cholestyramine or placebo treatment group. Because of missing or inconclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Our results support previous studies demonstrating that asymptomatic subjects with cardiac risk factors generally have normal ETT and perfusion scans. [7][8][9] In the Lipid Research Clinics trial, 9 only 8.3% of 3775 asymptomatic men with hyperlipidemia had exercise-induced ECG ischemia. In a study of middle-aged siblings of patients with premature CAD, the stress ECG was abnormal in only 10% and thallium imaging in 22%.…”
Section: Ebct For Detection Of Subclinical Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support previous studies demonstrating that asymptomatic subjects with cardiac risk factors generally have normal ETT and perfusion scans. [7][8][9] In the Lipid Research Clinics trial, 9 only 8.3% of 3775 asymptomatic men with hyperlipidemia had exercise-induced ECG ischemia. In a study of middle-aged siblings of patients with premature CAD, the stress ECG was abnormal in only 10% and thallium imaging in 22%.…”
Section: Ebct For Detection Of Subclinical Cadmentioning
confidence: 99%
“…1,2 Although the presence and extent of left ventricular ischemia can accurately identify individuals at high risk for cardiac events, [3][4][5][6][7][8] the low prevalence of a positive test result among asymptomatic subjects with cardiac risk factors mitigates against this approach. [7][8][9] Electron beam computed tomography (EBCT) is a new noninvasive technique that can detect coronary atherosclerosis even at its earliest stages on the basis of the presence and severity of coronary artery calcification. 10 Although calcification severity predicts the presence of significant anatomic CAD, 11,12 there is little information as to whether the coronary artery calcium score (CACS) can identify asymptomatic individuals at high risk for having myocardial ischemia among a larger, asymptomatic, heterogeneous population with cardiac risk factors.…”
mentioning
confidence: 99%
“…They reported that the risk of CHD mortality in association with a positive E-ECG test was 5.7-and 4.9-fold higher in the cholestyramine and placebo groups, respectively. 8 Their results suggested that E-ECG responses are a valuable and independent predictor of CHD mortality risk in men with hypercholesterolemia. Bigi et al 10 evaluated the importance of E-ECG for predicting mortality in hypertensive individuals with angina.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have reported on the efficacy of E-ECG stress testing for its ability to predict CHD in persons with MetS or the components of MetS. A double-blinded, placebo-controlled clinical trial was conducted by Ekelund et al 8 in an effort to determine if positive findings on E-ECG are predictive of CVD events in hypercholesterolemic men. They observed 3806 asymptomatic, hypercholesterolemic men for an average of 7.4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation